Efficacy of small-incision lenticule extraction surgery in high astigmatism: A meta-analysis - Cui, Ge; Di, Yu; Yang, Shan; Chen, Di; Li, Ying (Frontiers in Medicine, 2023)
Purpose This study aimed to evaluate the efficacy of small-incision lenticule extraction (SMILE) in improving vision and visual quality and correcting astigmatism for the treatment of high astigmatism. Methods Eligible studies and studies comparing the efficacy of SMILE with femtosecond laser-assisted laser in situ keratomileusis (FS-LASIK) or transepithelial photorefractive keratectomy (T-PRK) for high astigmatism (≥2.00 D) were identified in PubMed, Embase, and the Cochrane Central Register of Controlled Trials, searched from their inception to 29 May 2022. The references of all searched studies were checked as supplements. The risk of bias was evaluated for each eligible study. The literature was screened according to the inclusion and exclusion criteria, and relative data were extracted. Data were extracted and analyzed by ReviewManager 5.4. The primary outcome was post-operative uncorrected distance visual acuity (UDVA). The secondary outcomes included corneal aberrations and vector parameters. The weight mean difference (WMD) and their 95% confidence intervals (95% CI) were used to assess the strength of the association. Results A total of six studies including 380 astigmatism eyes were involved, with 211 high-astigmatism eyes and 31 low-astigmatism eyes undergoing SMILE surgery, 94 high-astigmatism eyes undergoing FS-LASIK surgery, and 44 high-astigmatism eyes undergoing T-PRK surgery. Compared with non-SMILE, SMILE induced more astigmatism (weighted mean difference [WMD] = −0.07, 95% CI [−0.12 to −0.02], P = 0.005) and fewer sphere aberrations (WMD = −0.12, 95% CI [−0.17 to −0.08], P < 0.00001). The post-operative UDVA, sphere, spherical equivalent (SE), and higher order aberrations in different surgeries were likewise equivalent. The difference vector and index of success were significantly higher, and the surgically induced astigmatism vector, correction index, and magnitude of error were significantly lower in SMILE. Conclusion This meta-analysis suggests that SMILE, FS-LASIK, and T-PRK show excellent efficacy, predictability, and safety for myopia. SMILE exhibited less astigmatism refraction predictability and less surgically induced spherical aberrations. There may be more under-correction in SMILE. More randomized, prospective, and large sample-sized studies are needed to confirm these conclusions in the long term.